PARENTING PATTERNS FOR LEARNING DISCIPLINE OF ELEMENTARY SCHOOL CHILDREN IN LANGENHARJO VILLAGE, PATI - Asnafun Naimah; Ika Oktavianti; Muhammad Noor Ahsin (PROGRES PENDIDIKAN, 2022)
This study aims to analyze the role of parenting on the learning discipline of elementary school age children in Langenharjo Village, Margorejo District, Pati Regency. This research uses a qualitative case study method. The data collection technique used is data training or in the form of in-depth observations, interviews and documentation. The subjects studied were school students in Langenharjo Village and their parents. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results showed that all parents provide a form of democratic parenting to their children. In the application of this parenting style, parents provide assistance and guide children in learning to apply discipline to children with full understanding. Parents also give freedom to children, but it must be accompanied by certain limits and rules for the good of the child which must be agreed upon by parents and children with various considerations and not burdensome to the child. Learning discipline, especially for children who attend SD Langenharjo 01, can be said to be going well, with democratic parenting applied by parents in dealing with learning conditions during a pandemic like this, students in studying and doing assignments can complete and collect assignments on time.